Analysis of Genetic Diversity in Sesame (Sesamum indicum l.) Germplasm using RAPD Markers and Disease Resistance Screening Through RGA Markers - Pujar, Rajendra B.; Patil, Chandrashekhar G. (Asian Journal of Biological and Life Sciences)
Sesame (Sesamum indicum L.) belongs to an angiosperm family Pedaliaceae. It is an ancient oilseed crop known to mankind and it is a diploid species. Its oil is highly priced as it consists of natural antioxidants. S. indicum has a large number of varieties and are susceptible to many pathogens. There is a huge yield loss due to an insect pathogen Antigastra catalaunalis, viral, bacterial and mycoplasma. In the present study, molecular characterization of 40 sesame germplasm from different geographical regions of the world and Indian accessions were included. The study was under taken to determine the extent of genetic diversity between the varieties at molecular level. OPA, OPB and OPM series of RAPD decamers were screened and a total of 150 amplified fragments were scored, out of which 122 fragments are polymorphic with an average of 7.62 polymorphic fragments per primer. The average percent polymorphism was 80.5 among the accessions studied. The similarity indices were ranging from 0.41 to 0.98. Cluster analysis was done by UPGMA (Unweighted Pair Group Method with Arithmetic Mean) based dendrogram. The results indicates that, with the use of a limited number of decamers, RAPD technique revealed a high level of polymorphism among the accessions and are reliable markers to assess the genetic diversity within sesame germplasm effectively for breeding programme. Screening for disease resistant varieties was carried out using RGA markers and two primers showed positive test for presence of ‘R’ gene in the sesame accessions and diploid wild species.